Analisis Troubleshooting Belt Scale CV509 pada Proses Pemindahan Batubara dalam Meningkatkan Performa dan Kehandalan Sistem Pengukuran di PT. BT - Ramadhan, Iqbal; Suwarni, Putri Endah; Nudin, Burhan (Fakultas Teknik Universitas Tulang Bawang, 2025)
The Belt Scale is a critical instrument in industries for measuring the flow rate of materials on conveyors. The accuracy of these measurements is crucial as it directly impacts production efficiency, costs, and product quality. This research aims to conduct an in-depth analysis of Belt Scale accuracy under various operational conditions. The methodology employed involves collecting field data, conducting literature reviews, and utilizing computer simulations. The acquired data is then compared against reference data to identify error rates and influencing factors. The anticipated outcome of this study is a deeper understanding of Belt Scale performance, enabling companies to optimize their measurement systems. Furthermore, this research paves the way for the development of more advanced material measurement technologies. The primary objective of this study is to enhance the reliability of Belt Scale measurement systems, thereby providing more accurate data and facilitating better decision-making in production processes. Keywords: Accuracy, Belt Scale, Industrial Conveyor, Material Measurement.